2003
DOI: 10.1097/00001756-200305230-00013
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of shape from shading

Abstract: Psychophysical studies have shown that human observers resolve shape-from-shading ambiguities by assuming that light is coming from above-left. Using event-related potentials (ERPs), we measured the processing time of the perception of an ambiguous shaded pattern. We found that the N2 component followed the change of perceived shape with stimulus orientation. We also found that the P1 component in occipital and temporal areas was correlated with the observers' idiosyncratic bias for light source position. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
4
16
0
Order By: Relevance
“…In contrast, the activity in higher visual areas (in particular in parietal areas) was not affected by lighting direction (left vs. right), but instead reflected the perceived shape (convex vs. concave). Past studies had already highlighted several regions of the shape-from-shading network, in particular early visual areas (5)(6)(7)(8)(9) and to a lesser extent higher extrastriate (10) and parietal areas (11). Our study helps delineating the functions mediated by these different cortical areas.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In contrast, the activity in higher visual areas (in particular in parietal areas) was not affected by lighting direction (left vs. right), but instead reflected the perceived shape (convex vs. concave). Past studies had already highlighted several regions of the shape-from-shading network, in particular early visual areas (5)(6)(7)(8)(9) and to a lesser extent higher extrastriate (10) and parietal areas (11). Our study helps delineating the functions mediated by these different cortical areas.…”
Section: Discussionmentioning
confidence: 51%
“…Previous neurophysiological and imaging studies have implicated several brain regions in the processing of shape-fromshading: primary visual cortex (V1) (5)(6)(7)(8)(9), areas in the caudal inferior temporal gyrus (10) and the inferior parietal sulcus (11). However, the functions mediated by these different cortical areas may differ.…”
mentioning
confidence: 99%
“…The right hemisphere is better for a whole variety of tasks. For example, Mamassian, Jentzsch, Bacon, and Schweinberger (2003) recently showed that a shape-from-shading task activates the right hemisphere of the brain more than the left. So what is special about the right hemisphere?…”
Section: Discussionmentioning
confidence: 99%
“…There are only two ERP studies that have reported relevant data. Mamassian, Jentzsch, Bacon, and Schweinberger (2003) presented ambiguously shaded patterns and examined VEPs. They found correlations bechange in voltage in the P1 latency range reflects an orientation effect over the occipital cortex in the latency range between 80 and 200 msec.…”
Section: Discussionmentioning
confidence: 99%